Parenting Capacity Assessment for the Court in a Multifamily Group Setting - Di Pasquale, Roberta; Rivolta, Andrea (Frontiers in Psychology, 2016)
Parenting capacity assessment in court evaluations is a particularly complex task, given that it is necessary to consider the vast array of distinct and interrelated aspects and abilities which represent parenting, as well as the elevated number of contextual levels that influence parenting quality. The perspective we want to introduce regards the potentiality of the multifamily group as the elective observational setting in parenting capacity assessment.